The philosophy of physical education a new perspective - Stolz, Steven A. (Routledge studies in physical education and youth sport, 2014)
The discipline area of physical education has historically struggled for legitimacy, sometimes being seen as a non-serious pursuit in educational terms compared to other subjects within the school curriculum. This book represents the first attempt in nearly thirty years to offer a coherent philosophical defence and conceptualisation of physical education and sport as subjects of educational value, and to provide a philosophically sound justification for their inclusion in the curriculum. The book argues that rather than relegating the body to "un-thinking" learning, a person's essential being is not confined to their rationality but involves an embodied dimension. It traces the changing conceptions of the body, in philosophy and theology, that have influenced our understanding of physical education and sport, and investigates the important role that embodiment and movement play in learning about, through and in physical education. Physical education is defended as a vital and necessary part of education because the whole person goes to school, not just the mind, but the thinking, feeling and acting facets of a person. It is argued that physical education has the potential to provide a multitude of experiences and opportunities for students to become aware of their embodiment, explore alternative modes of awareness and to develop insights into and new modes of being not available elsewhere in the curriculum, and to influence moral character through the support of a moral community that is committed to that practice. Representing a sophisticated and spirited defence of the educational significance and philosophical value of physical education and sport, this book will be fascinating reading for any advanced student or researcher with an interest in physical education, the philosophy of sport or the philosophy of education.